KALAMKARI AND PATTACHITRA VISUAL STORYTELLING AS HISTORY - Rincy T P (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This paper treats Kalamkari (Coromandel Coast) and Pattachitra (Odisha, with Bengal’s sung scrolls) as ways of making history visible. These pictures were never mere decoration. In temples, painted cloths stepped in for wooden icons at fixed moments in the ritual year, pinning down what the gods should look like and when they should appear. In village squares, performers unrolled long scrolls and sang the story as they revealed each scene, stitching myth, memory, and moral instruction into a shared timeline. In household workshops, families passed on the craft step by step—scouring and mordanting cloth, grinding pigments, burnishing grounds—so that colors “took,” lines held, and narratives read clearly. Technique and story moved together: the order of making reinforced the order of remembering. Read historically, Kalamkari and Pattachitra are living archives. They standardize sacred images, organize communal time through festivals and performances, and preserve practical knowledge in repeatable routines. The household—often with a gendered division of tasks—served as the archive’s engine, ensuring continuity across generations. Thus, visual storytelling here does not illustrate history from the outside; it does history from within—by fixing forms, pacing time, and keeping collective memory legible on cloth.